Assessing an Islamic Bank's Cash Flow - Ana Fitria (Department of Islamic Banking, 2022)
The cash flow statement is made up of three parts: operating, investing, and financing cash flows. The objective of this study is to determine the progress of cash flows as observed via changes or comparisons of cash flows at PT. Sharia Aceh Bank. The method adopted is a quantitative descriptive method, in which existing data from the bank's annual reports from 2017 through 2021 is collected and reviewed. The findings reveal that PT. Bank Aceh Syariah has fluctuating cash flow but is still able to maintain positive cash flow on average.